Novel engineering: integrating literacy and engineering design in a fifth grade classroom. (2nd January 2019) - Montgomery, Samantha; Madden, Lauren
Abstract: This article describes a new and unique context for integrating STEM and literacy instruction—Novel Engineering. Oftentimes, STEM design challenges are focused on developing solutions to the big problems that humans face such as cleaning up oil spills or contrived situations in which children are tasked with building solutions to hypothetical problems such as creating bridges or towers for the purpose of the challenge only. Though these types of learning experiences have merit and benefit students by developing problem-solving skills and bringing awareness to global issues, they are sometimes disconnected from the world outside the classroom. This article focuses instead on using conflicts within the storyline of children's books as the problem-solving context and has benefits for children in both language arts and STEM learning. We offer suggestions that classroom teachers across the K-6 spectrum could use to implement Novel Engineering in their own classrooms.